The dynamic nature of ageing: novel findings, therapeutic avenues and medical interventions - Chmielewski, Piotr Paweł (Anthropological Review, 2020)
Ageing is one of the most complex and difficult problems for humans to face and for science to solve. Although human senescence was viewed as a passive and uncontrollable process of deterioration over time with little or no genetic regulation, the concept that ageing is caused by both genetic and environmental factors is now generally accepted, even though it remains difficult to distinguish between ageing sensu stricto and the effects of age-related diseases. Empirical data show that mechanisms of ageing are highly conserved during evolution. Moreover, it has been established that there are specific molecular ‘instructions’ for ageing, which suggests that a better understanding of the molecular biology of ageing will open new possibilities regarding future interventions. The complexity of ageing diminishes the possibility that any general theory will completely explain this metaphenomenon. Likewise, it is highly unlikely that any medication can stop or reverse human senescence. Nevertheless, ageing as a dynamic and malleable metaphenomenon can be modulated by a variety of influences. The concept of the shrinkage of the homeodynamic space with age, i.e. homeostenosis, is especially interesting and intriguing as it shows that novel therapeutic approaches and rational strategies can help delay the onset of the ageing-associated pathologies by enhancing the homeodynamic capabilities of the body. The aim of this article is to present current data from evolutionary and molecular gerontology and discuss them within the ambit of this review which is devoted to the dynamic, emergent and plastic nature of human ageing and implications for future interventions.